Al-Usus al-'Ilmiyyah li Minhaj al-Bahth al-Usuli Dirasah Tahliliyyah - al-Zanki, Najm-Aldeen K. Kareem (Jurnal Fiqh, 2005)
This study refers to the contemporary calls pertaining to the renewal and modernization of the methods adopted by the founders of usul al-fiqh. It discusses three ideas; considering the Qur`an and Sound Sunnah initiative references to other evidences, omitting any general evidence that does not fulfill the conditions of certainty and utilizing only the maxims and roles that affect and benefit the actual life of the man.